(untitled) (Fiep Bulletin - online, 2014)
Regular sport activities decrease the risk of venous thrombosis as was proved in the population-based case-control study by van Stralen et al. A participation in sport activities reduces the risk of VTE compared to others doing no sport (OR 0.64; 95% CI 0.58-0.71) regardless of the differences in risks for various frequencies, intensities, and types of sport. But sport activities may lead in certain cases to cause VTE with potential fatal consequences. Hypercoaguability might be achieved by excessive perspiration without the adequate liquid supply, restriction of liquids or abuse of diuretics in order to „drawing“ muscles, polyglobulia due to training in high altitude or abuse of rythropoetin, using of contraceptives, abuse of anabolic steroids, former unknown inherited thrombophilia or malignancy. Travelling, wearing tight footwear or clothes, excessive abdominal press in bodybuilding participate in the stasis of blood. Damage of venous wall is daily problem in the collisional and contact sports. Prevention of VTE of a sportsman requires an acceptation of his priorities and goals by sports doctors. On the other hand, a sportsman, his coach and manager have to be well educated not only in medical prevention but also in nonmedical measures. The sportsman performing the sport at the high level or an enthusiast may be attacked by psychological press, high expectations, responsibility, doping and drugs. Principles of prevention of VTE in sportsmen: 1. be knowledgeable in signs of VTE , 2. adequate liquid supply, 3. don’t use diuretics in order to „drawing“ muscles, 4. don’t use anabolic steroids, 5. don’t use of doping, 6. be wakeful in using of contraceptives, 7. consider of screening inherited thrombophilia (genetic tests) in sportsmen, 8. consistent prevention of traveler’s thrombosis, 9. be wakeful in case of trauma. In the end of the presentation we present case report of student of Faculty of Physical Education and Sports, Alpine Ski of World Cup.